Differentiating the Degradation Phenomena in Silicon-Graphite Electrodes for Lithium-Ion Batteries. Issue 12 (1st January 2017) - Wetjen, Morten; Pritzl, Daniel; Jung, Roland; Solchenbach, Sophie; Ghadimi, Reza; Gasteiger, Hubert A.
Abstract : Silicon-graphite electrodes usually experience an increase in cycling performance by the addition of graphite, however, the relation of the silicon/graphite ratio and the aging mechanisms of the individual electrode and electrolyte compounds still requires a more fundamental understanding. In this study, we present a comprehensive approach to understand and quantify the degradation phenomena in silicon-graphite electrodes with silicon contents between 20-60 wt%. By evaluating the cycling performance and total irreversible capacity of silicon-graphite electrodes vs. capacitively oversized LiFePO4 electrodes in presence of a fluoroethylene carbonate (FEC)-containing electrolyte, we demonstrate that the aging of silicon-based electrodes can be distinguished into two distinct phenomena, which we describe as silicon particle degradation and electrode degradation. Cross-sectional scanning electron microscopy (SEM) images and a detailed analysis of the electrode polarization upon cycling complement our discussion. Further, we deploy post-mortem 19 F-NMR spectroscopy to (i) quantify to loss of moles of FEC in the electrolyte and correlate this with the amount of charge that was exchanged by the silicon-graphite electrodes, (ii) estimate the pore volume of the silicon-graphite electrodes that is occupied by FEC decomposition products, and (iii) derive implications for the relation of the electrolyte volume and cycle life of commercial silicon-based Li-ion batteries.